GERIATRIC PROBLEMS AWARENESS AMONG ADULTS IN RAWALPINDI: Awareness of Geriatric Problems - Misbah, Samreen; Kadir, Ehsan; Roshan, Rukhsana; Khan, Iqbal Ahmad; Rahman, Mahmood ur (Pakistan Armed Forces Medical Journal, 2015)
Objective: To assess the knowledge, attitude and practice (KAP) regarding elderly age health problems among adults of Rawalpindi. Study Design: Descriptive cross sectional study. Place and Duration of Study: Airport Housing Society Rawalpindi from July 2011 to Nov 2011. Material and Methods: A total of 200 households of age 50-59 years were included in the study by convenient sampling technique (115 males and 85 females). Adult population of the age 50-59 years with physical and mental disabilities were excluded from the study. Data collected after taking informed consent was analyzed by SPSS 17. Results: Mean age of respondents was 54.78 ± 3.41 years. Knowledge regarding age limit of senior citizens was 140 (70%). A total of 174 (87%) knew about increased incidence of fall with increasing age but only 53 (26.5%) did any practical change. About 152 (76%) considered that prior knowledge about geriatric age problems can help plan for old age; efforts to get information about elderly age problems were reported by 170 (85%). There was a significant association between level of knowledge and efforts to stay healthy (p<.001). The difference between level of knowledge of males and females was significant (p=.007). Conclusion: Prior knowledge among residents of the society was found to be a more preferred option to give people information about optimal aging, but this should be started at a much earlier time by facilitating information, to restore physical health to have a healthy and functional elderly individual in the society.